2003
DOI: 10.1091/mbc.e03-05-0315
|View full text |Cite
|
Sign up to set email alerts
|

Impairing Actin Filament or Syndapin Functions Promotes Accumulation of Clathrin-coated Vesicles at the Apical Plasma Membrane of Acinar Epithelial Cells

Abstract: In this article, we investigate the contributions of actin filaments and accessory proteins to apical clathrin-mediated endocytosis in primary rabbit lacrimal acini. Confocal fluorescence and electron microscopy revealed that cytochalasin D promoted apical accumulation of clathrin, alpha-adaptin, dynamin, and F-actin and increased the amounts of coated pits and vesicles at the apical plasma membrane. Sorbitol density gradient analysis of membrane compartments showed that cytochalasin D increased [14C]dextran a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
3
46
2
Order By: Relevance
“…The entire cell surface became highly irregular, presumably because of the normally stabilizing, cortical actin cytoskeleton was destroyed, so that a clear distinction between protrusions and bulk membrane was not possible (Figure 7, B and C). In agreement with other studies of the relation between the actin cytoskeleton and the clathrinmediated endocytosis (Gaidarov et al, 1999;Cao et al, 2003;da Costa et al, 2003), the number of clathrin-coated pits increased considerable. Most importantly, immunogold labeling did not reveal any ErbB2 in the coated pits ( Figure 7, B and C).…”
supporting
confidence: 92%
“…The entire cell surface became highly irregular, presumably because of the normally stabilizing, cortical actin cytoskeleton was destroyed, so that a clear distinction between protrusions and bulk membrane was not possible (Figure 7, B and C). In agreement with other studies of the relation between the actin cytoskeleton and the clathrinmediated endocytosis (Gaidarov et al, 1999;Cao et al, 2003;da Costa et al, 2003), the number of clathrin-coated pits increased considerable. Most importantly, immunogold labeling did not reveal any ErbB2 in the coated pits ( Figure 7, B and C).…”
supporting
confidence: 92%
“…Overexpression of PACSIN isoforms in NIH 3T3 fibroblasts inhibits transferrin uptake [11]. Introduction of the SH3 domain of PACSIN results in filamentous actin accumulation and impairment in endocytosis, as assayed by apical plasma membrane accumulation of α-adaptin and clathrin [5]. Here we show that PACSIN3 participates in the trafficking of GLUT1, but not GLUT4, in unstimulated 3T3-L1 adipocytes.…”
mentioning
confidence: 56%
“…Recent studies have identified adaptor proteins that do coordinate membrane trafficking events with alterations in the cytoskeleton. Major examples are the amphiphysin, cortactin, endophilin, intersectin and syndapin/PACSIN families [4][5][6][7]. These proteins contain multiple protein-protein interaction domains, which allow them to *Address correspondence to William Roach at present address: Department of Biochemistry, Dartmouth Medical School, Hanover, NH 03755-3844. william.roach@dartmouth.edu.…”
Section: Introductionmentioning
confidence: 99%
“…23 Digital image analysis and evaluation of A/D rab3D labeling ratios in multiple planes from z-stacks acquired from acini was as described previously. 54 Serial sections from confocal fluorescence microscopy images of nontransduced and Ad-LacZ-transduced acini of comparable size and thickness labeled to detect actin filaments and rab3D were acquired at equal gain and contrast intensities, pinhole size, image section thickness (0.6 mm) and zoom ( Â 2 zoom magnification, Â 60 objective). Initial gain and contrast levels were established using both samples to ensure that fluorescence levels were not saturated.…”
Section: Confocal Fluorescence Microscopymentioning
confidence: 99%